89.4k views
1 vote
How do i do this and what’s the answer????

How do i do this and what’s the answer????-example-1

1 Answer

4 votes

Answer:

The correct answer is z = -6.

Explanation:

1/3 (2z + 6) = 1/4 (z - 2)

The first step I am going to take is to multiply both sides of the equation by 12 (the least common multiple of 3 and 4). This will eliminate the fractions on both sides of the equations and make the numbers much easier to work with.

4 (2z + 6) = 3 (z - 2)

Next, we can use the distributive property to eliminate the parentheses. This means multiplying each term inside the parentheses by the coefficient on the outside of the parentheses.

8z + 24 = 3z - 6

Now, we can subtract 3z from both sides of the equation.

5z + 24 = - 6

Next, we should subtract 24 from both sides of the equation.

5z = -30

Finally, we can divide both sides of the equation by 5.

z = -6

Therefore, the correct answer is z = -6.

Hope this helps!

User Subarroca
by
5.2k points